Quality Assurance Practices Of Higher Education Institutions In China: Case Analysis - Fengyi Ma; Guangjun Tao (International Journal of Educational Management and Innovation, 2022)
This case study described the quality assurance practices andthe challenges faced by Higher Education Institutions inGuangxi Province, China. The study was carried out withtwelve (12) quality assurance focal persons from each publicUniversity in Guangxi, China. These focal persons have beeninvolved in the practice of quality assurance for at least threeyears. Moreover, findings reveal that the Teaching QualityMonitoring Department takes charge of the planning of theprograms, assisting colleges, and assessing and monitoring ofprograms subjected for accreditation and teaching qualityassurance. However, part of its challenges are limitedinvolvement of other professional institutions in the qualityassurance evaluation, overlapping duties, lack of trainingamong quality assurance staff, the development of teachingquality assurance scheme is incomplete, and utilization ofTeaching quality monitoring department is inadequate.Implications and recommendations were established toimprove quality assurance practices from the results.